Photocatalytic Material–Microbe Hybrids: Applications in Environmental Remediations - Yu, Yadong; Wang, Shanshan; Teng, Jinrui; Zupanic, Anze; Guo, Shuxian; Tang, Xiaobin; Liang, Heng (Frontiers in Bioengineering and Biotechnology, 2022)
Environmental pollution has become one of the most urgent global issues that we have to face now. Searching new technologies to solve environmental issues is of great significance. By intimately coupling photocatalytic materials with microbes, the emerging photocatalyst-microbe hybrid (PMH) system takes advantages of the high efficiency, broad-spectrum light capture capability of photocatalytic material, and the selectivity of microbial enzymatic catalysis to efficiently converse solar energy into chemical energy. The PMH system is originally applied for the solar-to-chemical production. Interestingly, recent studies demonstrate that this system also has great potentials in treating environmental contaminations. The photogenerated electrons produced by the PMH system can reductively decompose organic pollutants with oxidative nature (e.g., refractory azo dyes) under anaerobic circumstances. Moreover, based on the redox reactions happened on the surface of photocatalysts and the enzymatic reactions in microbes, PMH system can convert the valences of multiple heavy metal ions into less or even none toxic status simultaneously. In this review, we introduce the recent advances of using the PMH system in treating environmental pollutions, and compare this system with another similar system, the traditional ICPB (intimately coupled photocatalysis and biodegradation) system. Finally, the current challenges and future directions in this field are discussed as well.